Management of three endangered plant species in dynamic Baltic seashore meadows - Rautiainen, Pirjo; Björnström, Taina; Niemelä, Marika; Arvola, Pia; Degerman, Aija; Erävuori, Lauri; Siikamäki, Pirkko; Markkola, Annamari; Tuomi, Juha; Hyvärinen, Marko (Opulus Press Uppsala AB, 2007)
v 2007 ok